2014
DOI: 10.1016/j.carbon.2013.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of natural graphite flakes revealed by oxidation: Limitations of XRD and Raman techniques for crystallinity estimates

Abstract: The estimation of the active surface area (ASA) of various macrocrystalline graphitic materials is industrially valuable but the microstructures of these materials are still contestable. This in turn has led to difficulties in the unambiguous interpretation of crystallographic measurements with powder X-ray diffraction (pXRD) and Raman spectroscopy as well as their relationship to the ASA. To resolve this issue a systematic approach is required. As a starting point two widely accepted pXRD and Raman methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 65 publications
6
53
1
Order By: Relevance
“…A recent extensive investigation on natural flake graphite, very similar to the materials under consideration in this study, concluded that the flakes are comprised of polygonized stacks of interlinked crystals as seen from an angle in Figure 1A. [36]. The morphology is the result of complex crystal growth phenomena during flake formation.…”
Section: Discussionmentioning
confidence: 96%
“…A recent extensive investigation on natural flake graphite, very similar to the materials under consideration in this study, concluded that the flakes are comprised of polygonized stacks of interlinked crystals as seen from an angle in Figure 1A. [36]. The morphology is the result of complex crystal growth phenomena during flake formation.…”
Section: Discussionmentioning
confidence: 96%
“…Although in the last decade NG production has grown, at current rates it is estimated that production could be maintained for over 200 years. Currently, to prepare graphene, only high-purity graphite (more than 99.9% fixed carbon) is used [15,16]. To achieve this level of purity, silicate mineral impurities in the starting graphite must be removed by vaporization at ultra-high temperature or leaching in hydrofluoric acid [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The Hummers method tends to create large puffed regions during exfoliation, resembling a concertina. The reason for this may be the segmented stacking structure found in this type of graphite [31]. The gas phase material on the other hand shows a more evenly distributed expansion, due the 1 st stage intercalation, rather resulting in a lattice work structure as exemplified in Figure 10 (B).…”
Section: Modified Hummers Methodsmentioning
confidence: 95%
“…In all cases the so-called disorder or D-peak was practically absent, indicating that the residual damage present in the material cannot be detected by this method. This is not surprising given the fairly large size of the GNPs compared to the small spot size of the Raman laser [31].…”
mentioning
confidence: 97%
See 1 more Smart Citation